Unraveling septal perfusion abnormalities in Ebstein's anomaly: A case report contrasting PET MPI with myocardial reality - Haluk Alibazoglu, MD; Adam M Khalil; Deniz Alibazoglu; Ahmed Sherif, MD; Ahmed Bafadel, MD; Amany Hillis, MD; Hidayath A Ansari, MD; Hani Sabbour, MD; Buket Alibazoglu, MD; Rawan A Hussein, CNMT; Mohammed E Khalil, MD (Radiology Case Reports)
In Ebstein's anomaly, septal perfusion abnormality poses a challenge in traditional interpretations of myocardial blood flow. We report a single case of a 43‐year‐old female with known Ebstein’s anomaly who was referred for preoperative cardiac evaluation prior to bariatric surgery. Due to her multiple cardiovascular risk factors and vague chest discomfort, positron emission tomography (PET) myocardial perfusion imaging (MPI) and cardiac magnetic resonance imaging (MRI) were performed. PET MPI demonstrated a partially reversible septal perfusion defect involving 30% of the left ventricular myocardium with fixed (12%) and ischemic (18%) components, while gated images revealed preserved wall motion. Cardiac MRI confirmed normal septal wall thickness and no myocardial fibrosis. These findings suggest that dyssynchronous atrial contraction and a shortened diastolic perfusion window associated with atrialization of the right ventricle are responsible for the observed perfusion abnormality rather than coronary artery disease or myocardial scar.